1982
DOI: 10.1001/archderm.118.8.542
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrochlorobenzene treatment of alopecia areata

Abstract: Forty-two patients with alopecia areata were treated with local applications of dinitrochlorobenzene (DNCB); We used DNCB in two forms, an acetone solution applied weekly or a cream used every day, employing a wide range of DNCB concentrations. The concentration used was varied at the time of each application to produce a contact dermatitis. Seven patients experienced complete and lasting hair regrowth, 17 had poor results, and in 18 patients the treatment was a failure. Acquired tolerance to DNCB was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As De Prost et al [11] suggest the dis agreement can partially be due to the fact that many investigators did not define exact ly the criteria for good hair regrowth. Cer tainly, it is not proper to speak of success when the regrowth is incomplete and not esthetically acceptable.…”
Section: Commentmentioning
confidence: 99%
“…As De Prost et al [11] suggest the dis agreement can partially be due to the fact that many investigators did not define exact ly the criteria for good hair regrowth. Cer tainly, it is not proper to speak of success when the regrowth is incomplete and not esthetically acceptable.…”
Section: Commentmentioning
confidence: 99%
“…It is reported that hair loss is more severe in patients with Down's syndrome than in otherwise normal patients with alopecia areata (1). Recently DNCB treatment has been applied successfully (5). The mechanism by which hair growth is induced is still unknown, but it has been suggested that suppressor T-Iymphocytes may act on the specific cytotoxic cells directed against follicular structures (6).…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic use of DNCB has been much limited; therefore, the eventual side effects, particularly systemic, are not well known. Toxic effects of dinitrophenol, one of the metabolites of DNCB, including hepatic and renal cellular changes, convulsive seizures, and hyperthermia have been described (5). Happle (7) discouraged the use of DNCB treatment for alopecia areata because of a possible mutagenic effect observed in animals.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of complications during immunotherapy for alopecia areata by contact sensitizers such as dinitrochlorobenzene (DNCB) and squaric acid dibutylester (SAD BE) have already been described. The more important ones are: painful cervical adenopathy, almost constant during the early weeks of treatment, generalized eczema and urticaria (1)(2)(3), and depigmentation (2)(3)(4)(5)(6). There is also the risk of a new sensitization with compounds chemically unrelated to DNCB or SADBE.…”
mentioning
confidence: 99%